2018
DOI: 10.4236/oalib.1104516
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Abuse among Female Undergraduates in Tertiary Institutions in IMO State, Southeast Nigeria: Prevalence, Pattern and Determinants

Abstract: Introduction: Sexual abuse is a global public health problem that cuts across social class, cultures, tribes etc. and has permeated the fabrics of tertiary institutions and many work places as long as humans have reasons to interact. Aim: To determine the prevalence, pattern and determinants of sexual abuse among undergraduates in tertiary institutions in Imo State, Nigeria. Methodology: This study was a descriptive, cross sectional survey of 600 female students in tertiary institutions in Imo State Nigeria. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 20 publications
2
14
1
Order By: Relevance
“…Both the qualitative and quantitative findings showed there were incidences of sexual harassment, rape, and attempted rape in the study setting. In a previous study of tertiary educational institutions in Imo Sate, the prevalence of sexual violence as at the time of the study was found to be 15.2% (Duru et al, 2018), which is less than the findings in this study (21.9%). Although, the culture of silence has shrouded sexual violence in secrecy in Nigeria thereby making the statistics to be far from reality, the fact remains that sexual violence is still a regular occurrence in tertiary institutions in Nigeria.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Both the qualitative and quantitative findings showed there were incidences of sexual harassment, rape, and attempted rape in the study setting. In a previous study of tertiary educational institutions in Imo Sate, the prevalence of sexual violence as at the time of the study was found to be 15.2% (Duru et al, 2018), which is less than the findings in this study (21.9%). Although, the culture of silence has shrouded sexual violence in secrecy in Nigeria thereby making the statistics to be far from reality, the fact remains that sexual violence is still a regular occurrence in tertiary institutions in Nigeria.…”
Section: Discussioncontrasting
confidence: 91%
“…In Nigeria, sexual violence has been termed an epidemic as many cases have been reported in the past few years mostly among the young populations (Achunike & Kitause, 2014). A study conducted in tertiary institutions comprising universities, colleges of education, polytechnics, schools of nursing, and seminary schools in Imo State, Nigeria, indicated that the current and lifetime prevalence of sexual violence among the participants was 15.2% and 34%, respectively (Duru et al, 2018). Duru et al further stated that the commonest form of sexual violence experienced by the survivors was fondling and grabbing of sensitive body parts (52.5%).…”
Section: Introductionmentioning
confidence: 99%
“…6 Almost three-quarters have ever had sex. This is similar to sexual behaviour seen among students in Ilorin-Nigeria 27 ; lower compared to students in Spain 22 ; but higher than those reported among the similar population in Botswana, urban Nigerian cities and Kilimanjaro region of Tanzania. 7,20,34,35 This may be as a result of an increased liberal worldview among young people; a sense of freedom experienced; and a desire for sexual experimentation in the university environment.…”
Section: Discussionsupporting
confidence: 78%
“…This is similar to studies from Kilimanjaro-Tanzania, Botswana, Ilorin and south-south-Nigeria, Dodoma-Tanzania and Spain among students. 20,22,25,27,34,36 However, health facilities and healthcare workers are the commonest sources of information on contraception among similar populations in Kwadaso-Ghana and the emerging regions of Ethiopia. 29,31 Information on contraception from family members often come out of concern that a young person is sexually or about to be sexually active., and therefore the need for safe sex.…”
Section: Discussionmentioning
confidence: 99%
“…Gender-based violence is a global health problem that spans all social classes, cultures, tribes, and religions and has permeated our societies including tertiary institutions, worship places, workplaces and communities so far as humans have reason to interact with themselves [1]. While it is a fact that women suffer as victims of gender-based violence, recent researches has shown that men may also suffer as victims of gender-based violence.…”
Section: Introductionmentioning
confidence: 99%